The doctrine of hardship in contract law: comparative study - Savanets, Liudmyla; Poperechna, Hanna (Актуальні проблеми правознавства, 2022)
The article analyzes the doctrine of hardship in the contract law of Ukraine, France, Germany, England. The grounds for modifying or terminating the contract due to a hardship are analyzed. A comparative analysis of the court’s powers to modify the contract in connection with a hardship is carried out. In French civil law the doctrine of l’imprévision covers all situations in which a party’s contractual obligations have become harder and more onerous to perform because of an unforeseen event posterior to the conclusion of the contract. The conception of hardship was introduced to Ukrainian Civil Code in 2004 for provide the contractual parties to overcome the negative impact of a change of circumstances that was unforeseeable at the time of the conclusion of the contract and renders performance excessively onerous for one of them. This provision is aimed, on the one hand, to restore the balance of interests in contractual relations and to reduce risks, and on the other hand, to keep the contract, as far as possible, preference given to the adaptation of the contract over its termination. Unfortunately, the case law indicates difficulty in implementing the provision of hardship. In English law doctrine is formed the concept of frustration. The only remedy for frustration in common law is termination of the contract; and termination is permanent – English law does not recognize partial frustration nor temporary frustration.German doctrine of hardship has been conceptualized into three aspects requiring a change of circumstances, the parties would not have concluded the contract if they had been aware of this change, and it would not be equitable for one party to deny the other party any amendment of the contract. German approach has been adopted in many harmonization projects and international instruments of contract law, in particular Principles on European Contract Law, Draft Common Frame of Reference, UNIDROIT Principles of International Commercial Contracts. In French, English and Germany law is established three different approaches to cases of contractual impossibility as an exception to pacta sunt servanda: contractual parties are not discharge unless performance has become impossible; as exception for impossibility to some cases; or as separate exception. The main problem nowadays is the lack of definition of “significant change of circumstances” in Ukrainian legislation and case law. Such a rule seems to increase legal uncertainty as the criteria of its implementation are vague and have not yet been firmly and precisely defined by case law. In most cases, the courts do not recognize the change of circumstances referred to by the party as significant.Ukrainian civil law doctrine defines “significant change of circumstances” as change of circumstances that did not depend on the will of parties and was the result of certain actions from the outside; and contains four features: was unforeseeable at the time of the conclusion of the contract, its duration and inevitability, arise without fault of the parties.The law of many states and international soft law gives courts power to modify or terminate the contract in case of change in circumstances. French Civil Code not contains certain grounds in the event of change in circumstances to modify or terminate the contract. They are the same as in case of contract modification or termination by parties. In contrast, Ukrainian legislator decreases significantly judicial intervention in contractual relations. The power of Ukrainian courts to modify the contract is based on the general principles of contractual freedom, if parties in contractual terms lay down modification the contract in case of change in circumstances that was unforeseeable at the time of the conclusion of the contract renders performance excessively onerous for a party.